539 views
2 votes
3(7x – 8x) + 6 = 5(-2 - 7x) + 4

User Raksha
by
5.8k points

2 Answers

4 votes

Answer:

x=-3/8

Explanation:

Isolate the variable by dividing each side by the factors that don't contain the variable.

User Rotem B
by
5.2k points
2 votes

Answer:

x= −3/8

Explanation:

Step 1: Simplify both sides of the equation.

3(7x−8x)+6=5(−2−7x)+4

3(7x−8x)+6=(5)(−2)+(5)(−7x)+4(Distribute)

−3x+6=−10+−35x+4

−3x+6=(−35x)+(−10+4)(Combine Like Terms)

−3x+6=−35x+−6

−3x+6=−35x−6

Step 2: Add 35x to both sides.

−3x+6+35x=−35x−6+35x

32x+6=−6

Step 3: Subtract 6 from both sides.

32x+6−6=−6−6

32x=−12

Step 4: Divide both sides by 32.

32x/32= −12/32

x= −3/8

User Billy Brown
by
5.6k points